Patterns and Trends of Herbal Medicine Use among Patients with Gynecologic Cancer - Theuser, Anna Katharin; Hack, Carolin; Fasching, Peter; Antoniadis, Sophia; Grasruck, Katharina; Wasner, Sonja; Knoll, Stefanie; Sievers, Hartwig; Beckmann, Matthias; Thiel, Falk C. (Geburtshilfe und Frauenheilkunde, 2021)
Background More and more information about complementary and integrative medicine is becoming available, especially among cancer patients. However, little is known about the use of herbal medicine by patients with gynecologic cancers. This study aimed to assess the use of herbal products by gynecologic cancer patients compared with healthy controls. Methods This cross-sectional study was conducted at the Department for Gynecology and Obstetrics of Erlangen University Hospital and included 201 patients with gynecologic cancer and 212 healthy controls. Use of herbal medicines was evaluated using a standardized questionnaire. Medical information on cancer patients was collected from hospital records. Group comparisons were done using a logistic regression model. Risk ratios were assessed using a Poisson regression model. Results Gynecologic cancer patients used herbal medicine significantly less often than healthy persons. 69% of gynecologic cancer patients and 81% of healthy participants reported using herbal products. 40% of cancer patients and 56% of healthy persons reported using plants for medicinal purposes. Motives of cancer patients for using herbal medicine included treatment of cancer-related symptoms. The major source of information for both groups was family and friends. Conclusions Although herbal medicine was used less by patients with gynecologic cancer, herbal products were used by both cancer patients and healthy individuals. To provide cancer patients with optimal therapy, oncologists should be informed about the herbal products used by their patients as this will allow them to take their patients' self-medication with herbal medicine into account. Counseling by oncologists on the use of herbal medicine should be encouraged.
CRIS-Team Scopus Importer:2021-07-02
Keywords: cancer; complementary and alternative medicine; gynecologic oncology; herbal medicine; integrative medicine